خصائص البنك ، الهيكلية المالية ، وأداء البنك - العبادي، محمد عيسى مفلح عليان; الخداش، حسام الدين مصطفى (جامعة الكويت - مجلس النشر العلمي, 2006)
هدفت هذه الدراسة إلى اختبار درجة اعتمادية الاقتصاد الأردني على السوق المالي مقارنة بالسوق المصرفي، كما هدفت إلى اختبار أثر الهيكلية المالية والخصائص البنكية على الأداء المصرفي، ممثلا بالربح المحاسبي وهامش سعر الفائدة. أظهرت النتائج استجابة ذات دلالة إحصائية للأداء المصرفي تجاه الزيادة في نسب رأس المال والديون؛ لتعكس أهمية ملاءمة نسب رأس المال ومحافظ الديون على الأداء المصرفي. دلت النتائج على أن البنوك ذات مستويات رأس المال العالية تواجه مستويات أدنى من تكاليف التمويل بوصفها استجابة لانخفاض احتمالية تكاليف الإفلاس. أظهرت النتائج المتعلقة بالهيكلية المالية انخفاض مستويات هامش سعر الفائدة والربحية، وهو الأمر الذي يعزى إلى زيادة مستويات البيئة التنافسية في السوق المصرفي الأردني. أظهرت النتائج أيضا أن البنوك غير الرئيسة قد حققت مستويات أقل من الأداء، وهو ما يعكس مستويات أقل من تكاليف التشغيل والتكاليف الإضافية، دلت هذه النتيجة على اعتمادية أكبر للبنوك غير الرئيسة تجاه الودائع بوصفها مصدر للتمويل، ويمكن من خلال ذلك استنتاج أن مستويات الأداء للبنوك الرئيسة ستكون أفضل في الظروف التضخمية والبيئة الضريبية المرتفعة، ويعكس ذلك قدرة هذه البنوك على تحميل جزء من التكاليف الضريبية والتكاليف الإضافية إلى عملائها. This study investigates whether the Jordanian economy is considered as a bank or more a market-based economy, reflecting the level of the relative reliance on banks vs. market finance. As a further concern, this study also tests whether financial structure (levels of bank and stock market developments), together with bank characteristics have zero impact on bank performance, typified by the banks accounting profits and interest rate margins. The evidence revealed that banks performance measures responded significantly to the increase in capital and loan ratios, reflecting the fact that adequate capital ratios and loan portfolios have empirical evidence in explaining performance measures. The results also showed that well capitalized banks achieved higher net interest rate margins and more profitability, implying that banks with higher capital ratios tend to face lower funding costs due to lower probability of bankruptcy costs. For their part, the financial structure results indicated that with more competitive banking industry, in which total banks assets constitute a larger proportion of GDP, lower interest rate margins and profitability have been reached. This shows that more bank development creates tougher competition, causing higher efficiency, and hence lowers profits, and in turn, lower interest rate margins. On sub-sample basis, the results indicated that non-major banks have experienced. on average terms, lower performance measures, reflecting lower operating costs, lower overhead costs and lower pre-tax profitability. This result shows more reliance from non-major banks toward deposits as main funding costs, leading to the conclusion under which major banks tend to profit more in inflationary and high-lax environments. This also indicates that major banks are more able to pass on at least part of their taxes and overhead expenses to their clients, in the form of lower deposit rates and/or higher loan rates.
أصل المقال منشور باللغة الإنجليزية
728795
Keywords: أسعار الصرف -- الأسواق المالية -- الأردن -- السياسة الاقتصادية -- مستخلصات الأبحاث -- السياسة المالية -- البنوك -- الديون -- المحاسبة الضريبية